1997
DOI: 10.1093/humrep/12.suppl_1.134
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain and cardiovascular risk factors in the post-menopausal woman

Abstract: Cardiovascular disease is the leading cause of mortality and morbidity in the post-menopausal woman. The natural menopause does not appear to be an independent risk factor (or a minor one) for coronary heart disease. Obesity, more precisely excessive intra-abdominal fat, is a cardiovascular risk factor especially with regard to the metabolic risk factors associated with this type of obesity. There is a progressive increase in weight gain at the age of menopause but this weight gain is related to ageing indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…A maioria dos estudos em que se acompanha a RCQ analisa grupo controle e pacientes em TRH após períodos de um a quinze anos (2,(23)(24)(25)(26). Observamos redução da RCQ bastante precoce, já no primeiro mês.…”
Section: Dosagens Hormonaisunclassified
“…A maioria dos estudos em que se acompanha a RCQ analisa grupo controle e pacientes em TRH após períodos de um a quinze anos (2,(23)(24)(25)(26). Observamos redução da RCQ bastante precoce, já no primeiro mês.…”
Section: Dosagens Hormonaisunclassified
“…This finding is a source of concern as they are often untrained and help to perpetrate the vicious circle of counterfeit and death [27]. The Unfriendly attitude of health workers, perceived high cost of hospital services lack of drugs and basic laboratory services, non availability of a regular physician on seat at the facility and delays in services in hospital could have accounted for this [28]. Health care providers need to treat the person from a lifestyle management perspective.…”
Section: R F Ara Et Al Open Journal Of Obstetrics and Gynecologymentioning
confidence: 99%
“…In this perspective establishment of a "health care corner for perimenopausal women" would be a good step to address this health issue. So the women can perceive menopause as an opportunity to concentrate on new activities and bring out the best in her [28].…”
Section: R F Ara Et Al Open Journal Of Obstetrics and Gynecologymentioning
confidence: 99%
“…Its de ciency contributes to the development of insulin resistance and diabetes mellitus. 3 Some other study reported that greater increased in waist-to-hip ratio and waist circumference, body mass index in postmenopausal women than that of premenopausal women. [10][11][12] Opposite nding was reported by some investigators who did not nd any signi cant di erence in BMI value in premenopausal and postmenopausal women.…”
Section: Introductionmentioning
confidence: 95%
“…It is associated with premature atherosclerosis, as well as with many metabolic alteration including insulin resistance, dyslipidemia and hypertension. 3 ere is a progressive increase in weight in postmenopausal women. It is represented by central redistribution fat with decrease in gluteofemoral fat and increase in intra-abdominal fat.…”
Section: Introductionmentioning
confidence: 99%